DAYA HASIL DAN KANDUNGAN LEMAK BEBERAPA VARIETAS SORGUM (Sorghum bicolor (L.) Moench) YANG DIBERI BEBERAPA DOSIS PUPUK FOSFOR - Trio Siswanto; Elza Zuhry; Nurbaiti ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This research aims to determine yield ability and fat content of some sorghum varieties with treated by some doses phosphorus fertilizer. This research was conducted from March to August 2014 at the Plant breeding experimental station Faculty of Agriculture Riau University. The experiment has conducted using randomized complete block design (RBD) 3 replications The first factor was the variety type which consist of Kawali, Numbu, Pahat, Mandau. The second factor was Phosphorus fertilizer dose which consists of 3 levels: 45 kg of SP-36/ ha, S2 = 90 kg of SP-36 /ha, S3 = 135 kg of SP-36/ha). Parameters those observed were days to flowering (day), crop age (day), panicle length (cm), seed weight per panicle (g), 1000 seed weight (g), seed weight per m2 and fat content.  The mean separation of analysis of variance was tested using Duncan’s multiple range test at 5%. The result indicates that of Phosphorus fertilizer 90 kg/ha showed the best result at Kawali varieties (8,1 ton/ha), Pahat (8,5 ton/ha) and Mandau (8,7 ton/ha), treated of Phosphorus fertilizer 90 kg/ha showed the best fat content at Numbu varieties (3,35 %) and Pahat (3,18 %).   Keyword: Sorgum bicolor, Phosphorus , Fat content, Yield Ability